Issues and challenges of period poverty during the Covid-19 pandemic in Malaysia - Norhafizah Ahmad,; Latifah Abdul Majid, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Menstruation is the blood that comes out of a woman’s cervix through the vagina at a certain time, and is not the cause of childbirth. The onset of menstruation is one of the signs of a woman’s puberty. In fact, puberty is a new challenge, especially for women, because it requires careful personal hygiene, whether before, during, or after menstruation. In Malaysia, women still suffer from period poverty and cannot afford sanitary pads due to financial constraints. This causes greater harm to women. Therefore, the main objective of this article is to identify the issues and challenges faced by women due to period poverty, especially during the Covid-19 pandemic. In this qualitative study, a document analysis from journal articles, books, and related materials was conducted. Findings suggest that women face significant challenges when it comes to period poverty. These include lack of affordable menstrual products, disadvantages in menstrual hygiene infrastructure, and negative stigma in the community. The implication of this study is to help women cope with the challenges of period poverty and to prepare for the onset of menstruation with sufficient knowledge and needs.